A DEVELOPMENT OF PREVENTION AND TREATMENT OF ANTERIOR CRUCIATE LIGAMENT INJURIES: AN INNOVATIVE ELECTRONIC EDUCATION MODEL - Zukirman, Syella Martha Bipu; Junaidi; Wahyuningtyas Puspitorini; Kuswahyudi (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
This study aims to develop an educational application for the prevention and treatment of ACL injuries, named ACL FRIEND. The content of this application consists are: ACL injury education and ACL grade 1 injury exercise programs. This research was conducted using a research and development method, from the ADDIE model. The research procedure consisted of five stages: Stage 1. Preliminary study (Analysis); Stage 2. Application design; Stage 3. Application development; Stage 4. Implementation; Stage 5. Evaluation. The model evaluated and validated by experts from the exercise therapy lecturer and experts from the sports medicine doctor. From the product feasibility testing results, the final percentage analysis of the ACL FRIEND application falls within the 84% range, indicating that the ACL FRIEND application is categorized as Very Good to used. The application ACL FRIEND can get on Google Playstore with free access.